Sports idols of senior athletes - Jelena Ilić (University of Banja Luka, Faculty of physical education and sport, 2013)
The aim of this paper is to identify idols of senior athletes. And based on the identification of idols some conclusions can be made with respect to the system of values some person. The sample included 318 Serbian professional senior athletes (183 male and 135 female), 18 to 40 years old. Respondents were engaged in 28 different sports, mostly volleyball, water polo, basketball, karate, bocca, savate, handball, kyokushin. The independent variables were gender and selected idol and dependent variables were sport, gender, actuality and origin of idol. Senior athletes for their sports idols, in most cases elect Roger Federer, Michael Jordan, Milorad Čavić. It turns out that the majority of male and female athletes are selected for their idol person that comes out of their sport, but also that there are some differences in the choice of idols and characteristics of idols in male and female athletes.